The little sisters of Eluria - David, Peter (Peter Allen); King, Stephen, 1947-; Furth, Robin, 1965-; Ross, Luke; Isanove, Richard; King, Stephen, 1947- (New York: Gallery 13, 2019)
Enter once more the world of Roland Deschain--and the world of the Dark Tower. Now near death following a vicious attack by the inhuman Slow Mutants, Roland is detoured from his relentless pursuit of the Man in Black and is taken in by a mysterious and unearthly group of nuns who specialize in anything but the healing arts. These hideous, corpselike creatures--the Little Sisters of Eluria--have murder on their twisted minds. And in his current condition, there's almost nothing the last gunslinger can do to prevent their tender mercies from taking hold.
"Contains material originally published in magazine form by Marvel Comics as Stephen King's the Dark Tower: The Gunslinger - The Little Sisters of Eluria #1-5"--Title page verso.
SHS
In English
Keywords: Roland (Fictitious character : King); Fantasy -- Comic books, strips, etc; Good and evil -- Comic books, strips, etc; Gunfighters -- Comic books, strips, etc; Heroes -- Comic books, strips, etc; Magic -- Comic books, strips, etc; Monsters -- Comic books, strips, etc; Nuns -- Comic books, strips, etc; Roland (Fictitious character : King) Comic books, -- Comic books, strips, etc; Comic books, strips, etc; Fantasy comic books, strips, etc; Fantasy fiction; Good and evil; Graphic novels; Gunfighters; Heroes; Magic; Monsters; Nuns; Comic books, strips, etc; Comic books, strips, etc; Comics (Graphic works); Comics (Graphic works); Graphic novels